New Records of Seagrass Flora in Air Bangis West Sumatera - Kamal, Eni; Bujang, Japar Sidik; Zakaria, Muta Hara (Jurnal Natur Indonesia, 2010)
Seagrasses in the Air Bangis Archipelago, west coast of Sumatra were found growing in sandy muddy substratesof the shallow coastal waters at depth of 0.3-2.5 m, dominated by degraded coral reefs around the off-shoreislands. Two species; Enhalus acoroides (L.f) Royle and Thalassia hemprichii (Ehrenb) Aschers were observed atPulau Unggas, Pulau Pasir Panjang and Teluk Tapang. Halodule uninervis (Forssk) Aschers was observed in twolocations; Pasir Panjang and Teluk Tapang. The occurrence of this species is unknown previously and therefore itis a new flora record for Sumatra. With this new record, Sumatra has six species of seagrasses, contributing tohalf of total number of seagrasses occurring in Indonesia. According to leaf width measurements, two morphologicalvariants (narrow and wide leaved) can be distinguished for Halodule uninervis. In addition, descriptions of thespecies and their habitat characteristic are provided.